PENGARUH PENERAPAN SRHRM DENGAN DUKUNGAN KARYAWAN BAGI KEGIATAN CSR EKSTERNAL PERUSAHAAN DI JAKARTA DAN SEKITARNYA - Goputra, Gionardy; Michael, Sebastian (JURNAL LENTERA BISNIS, 2020)
This study aims to look at the relationship between Socially Responsible Human Resource Management (SRHRM) and employee support for the perception of Corporate Social Responsibility (CSR). The data collection method used for the research is through surveys, which are distributed to employees of several companies in various industries in Indonesia and the collected data are analyzed using the Structural Equation Modelling (SEM) method. The findings of this research suggest that SRHRM practices will affect employee support for external CSR through the creation of a socially responsible organizational climate. Therefore, it should be considered by companies in Indonesia throughout its operations particularly for the company’s human resource department. This research contributes to expanding the CSR and HR literature which is still uncommon particularly in Indonesia.Keywords: Corporate Social Responsibility, Organizational Climate, Socially Responsible Human Resource Management